SOME BIOLOGICAL OBSERVATIONS ON A HORNET Vespa tropica var. pulchra (Du Buysson), with special reference to its dependence on Polistes wasps - SAKAGAMI, SHOICHI F; FUKUSHIM, KUNI'ICHI (Treubia, 2016)
-